MicroRNA-138 Inhibits Periodontal Progenitor Differentiation under Inflammatory Conditions. (February 2016) - Zhou, X.; Luan, X.; Chen, Z.; Francis, M.; Gopinathan, G.; Li, W.; Lu, X.; Li, S.; Wu, C.; Diekwisch, T.G.H.
Inflammatory conditions as they occur during periodontal disease often result in decreased alveolar bone levels and a loss of connective tissue homeostasis. Here we have focused on the effect of microRNA-138 (miR-138) as a potential regulator of periodontal stem cells as they affect homeostasis during inflammatory conditions. Our data indicate that miR-138 was significantly upregulated in our periodontal disease animal model. Interaction of miR-138 with a predicted targeting site on the osteocalcin (OC) promoter resulted in a 3.7-fold reduction of luciferase activity in promoter assays compared with controls; and miR-138 overexpression in periodontal progenitors significantly inhibited OC (3.4-fold), Runx2 (2.8-fold), and collagen I (2.6-fold). Moreover, treatment with inflammatory modulators such as interleukin (IL)–6 and lipopolysaccharide (LPS) resulted in a significant 2.2-fold (IL-6) or 1.9-fold (LPS) increase in miR-138 expression, while OC and Runx2 expression was significantly decreased as a result of treatment with each inflammatory mediator. Further defining the role of miR-138 in the OC-mediated control of mineralization, we demonstrated that the LPS-induced downregulation of OC expression was partially reversed after miR-138 knockdown. LPS, miR-138 mimic, and OC small interfering RNA inhibited osteoblast differentiation marker alkaline phosphatase activity, while miR-138 inhibitor and OC protein addition enhanced alkaline phosphatase activity. Supporting the role of OC as an essential modulator of osteoblast differentiation, knockdown of miR-138 or addition of OC protein partially rescued alkaline phosphatase activity in periodontal ligament (PDL) cells subjected to LPS treatment. Our data establish miR-138 inhibitor as a potential therapeutic agent for the prevention of the bone loss associated with advanced periodontal disease.